MANAJEMEN SIARAN PENDIDIKAN DI PROGRAMA 1 (SATU) RADIO REPUBLIK INDONESIA (RRI) PEKANBARU - Dwiva Devi Shintia; Azhar Azhar; Hadriana Hadriana (Jurnal Manajemen Pendidikan Penelitian Kualitatif, 2019)
The purpose of this study to describe and analyze the Management of Educational Broadcast inPrograma 1 (one) Radio Republik Indonesia (RRI) Pekanbaru viewed from the management functions of planning, organizing, actuating, and controlling. This study used descriptive qualitative method. Data collection was done by observation, interview, and documentation. The analysis technique used in this research is by Miles and Huberman method (1992) that is through data reduction process, data presentation, conclusion and triangulation.The results of the study show that the Education Broadcasting Management in Programa 1 (one) Radio Republik Indonesia (RRI) Pekanbaru has been running well. The first step of planning is a program that runs every year to create educational programs. Next determine the educational broadcast team, broadcaster, educational theme, broadcast schedule and resource person. Resource persons are carefully selected to provide accurate information. Planning in the studio engineering section is done matrang by providing guidance to the lookbook given to the broadcaster as a guide during the broadcast. Organizing educational broadcast in Programa 1 (one) RRI Pekanbaru is done by forming Team by Head of LPP RRI Pekanbaru prepared at the time of program of yearly program or have according to SK respectively if status of civil servant and given authority with clear job description. Implementation of education broadcast In Programa 1 (one) RRI Pekanbaru has been implemented in accordance with Government Regulation of the Republic of Indonesia Number 12 Year 2015 on Radio Public Broadcasting Institution of the Republic of Indonesia and KPI regulations on Broadcasting Conduct Manual (P3) of 2012. Supervision in RRI All Indonesia is conducted by Supervisory Board The highest position in RRI. RRI Pekanbaru supervision conducted by the Head of LPP RRI Pekanbaru. For the supervision of the broadcast program conducted by the head of broadcast program with the head of the planning and evaluation section of the program in Programa 1 (one) Pekanbaru conducted by Section Head of Programa 1 (one).